Congenital Malformations in Bovine - PARRAH, J D; MAKHDOOMI, D M; MOULVI, B A (The Indian Journal of Animal Reproduction, 2023)
The paper documents congenital malformations in bovine presented during last 15 years. An overall incidence of 0.4% of bovine congenital malformations was recorded. The percentage of malformation was higher in male calves (54.72%) than female calves (44.84%). Highest prevalence of congenital malfonnations (49.4%) was recorded in cross bred Jersey calves followed by 30.4% and 19.76% in cross bred Holsteins and local non- descript calves, respectively. Congenitally defective calves were born more to primiparous dams (56.24%) than to pleuriparous dams (43.32%). Still born defective calves recorded were 7.6%, where as only 5.3 % cases were born with dystocia. Highest number of congenital defects (31.16%) was related with digestive system with Artesia ani as the single most prevalent deformity (13.68%) among all recorded defects. Only 3.04% udder defects were recorded in Primiparous heifers.